Propagation Techniques and Agronomic Requirements for the Cultivation of Barbados Aloe (Aloe vera (L.) Burm. F.)—A Review - Cristiano, Giuseppe; Murillo-Amador, Bernardo; De Lucia, Barbara (Frontiers in Plant Science, 2016)
Barbados aloe (Aloe vera (L.) Burm. f.) has traditionally been used for healing in natural medicine. However, aloe is now attracting great interest in the global market due to its bioactive chemicals which are extracted from the leaves and used in industrial preparations for pharmaceutical, cosmetic and food products. Aloe originated from tropical and sub-tropical Africa, but it is also now cultivated in warm climatic areas of Asia, Europe and America. In this review, the most important factors affecting aloe production are described. We focus on propagation techniques, sustainable agronomic practices and efficient post harvesting and processing systems.